2004
DOI: 10.1002/bsl.619
|View full text |Cite
|
Sign up to set email alerts
|

From discretion to disagreement: explaining disparities in judges' pretrial decisions

Abstract: Judges are afforded considerable discretion in decision-making. Through their exercise of discretion, judges construct society's notion of crime and justice. This study examined 61 lay judges' bail decision-making in the English criminal justice system. The law states that in particular cases decisions to grant bail or remand in custody should be based on the risk of a defendant absconding, offending, or obstructing justice while on bail. However, there is little guidance on how these judgments should be made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…This result is consistent with judges' differences postulated by Baum (2010), the judicial disagreement explored by Dhami (2005) and also the disparity pattern found by Maguire (2010). These differences appear, in our data, in terms of both structure and content.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with judges' differences postulated by Baum (2010), the judicial disagreement explored by Dhami (2005) and also the disparity pattern found by Maguire (2010). These differences appear, in our data, in terms of both structure and content.…”
Section: Discussionsupporting
confidence: 93%
“…9(a-d). 13 As might be expected, given this scope for discretion in bail decision making and the lack of guidance in this area, research has found considerable variability in how decisions are made (see, for example, Dhami (2005), Hucklesby (1997) and various studies cited therein). Nonetheless, where bail is refused in instances where the statutory right to bail applies, the court is under a duty to explain its decision, and provide reasons for the refusal.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, it can take into account any other matters deemed to be 'relevant' thereby affording decision makers considerable discretion (Dhami 2005). 13 Yet there has been remarkably little guidance offered to the courts on how this discretion should be exercised.…”
mentioning
confidence: 99%
“…In other words, the prosecutors' recommendations predicted bail decisions in the observed cases 54 . These findings, showing little correspondence between what judges articulated as primary considerations motivating their decisions and their actual behaviour, were replicated in the UK in a series of archival and experimental studies of bail decisions 55 . The magistrates are required to state reasons for imposing conditions on bail.…”
Section: Correspondence Between Articulated Reasons and Decision Makingmentioning
confidence: 93%